2021
DOI: 10.3390/polym13091430
|View full text |Cite
|
Sign up to set email alerts
|

TD-DFT Simulation and Experimental Studies of a Mirrorless Lasing of Poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(1,4-diphenylene-vinylene-2-methoxy-5-{2-ethylhexyloxy}-benzene)]

Abstract: In this work, we investigate the TD-DFT simulation, optical, and mirrorless laser properties of conjugated polymer (CP) Poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(1,4-diphenylene-vinylene-2-methoxy-5-{2-ethylhexyloxy}-benzene)], also known as (PFO-co-PPV-MEHB) or ADS125GE. TD-DFT calculations were performed for three monomer units with truncated tails using time-dependent density functional theory (TD-DFT) calculations. The calculations showed a highest occupied and lowest unoccupied molecular orbital (HOMO-LUMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For the same system, Liu’s group [ 11 ] and Debkumar’s team [ 12 ] made a detailed theoretical study that describes the structure and the optoelectronic parameters of the different oligomers, which are indicated that the variation of the energy depends on the number of monomeric in each oligomer. Moreover, Mamduh J. Aljaafreh et al investigated the theoretical optoelectronic properties of an optimized structure of a copolymer that is based on MEH-PPVB and compared the obtained results with the experimental [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the same system, Liu’s group [ 11 ] and Debkumar’s team [ 12 ] made a detailed theoretical study that describes the structure and the optoelectronic parameters of the different oligomers, which are indicated that the variation of the energy depends on the number of monomeric in each oligomer. Moreover, Mamduh J. Aljaafreh et al investigated the theoretical optoelectronic properties of an optimized structure of a copolymer that is based on MEH-PPVB and compared the obtained results with the experimental [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The laser experimental set-up and formation of the ZnO- 5d random optical gain loop is depicted in Figure 8 (modified version of ref. [ 31 , 32 ]). To achieve transverse pumping, the third harmonic (355 nm) of a 5 ns Nd:YAG laser was focused by a quartz cylindrical lens (5 cm focal length).…”
Section: Methodsmentioning
confidence: 99%
“…We optimized the structure in Avagadro 0.2.0 software and later exported the input file to G16. We calculated many properties using simulations; however, in this study, we included only Frontier Molecular Orbital (FMO) structures [18].…”
Section: Computational Studiesmentioning
confidence: 99%
“…Polymers 2023, 15, x FOR PEER REVIEW 5 of 18 file to G16. We calculated many properties using simulations; however, in this study, we included only Frontier Molecular Orbital (FMO) structures [18]. Figure 2a presents the FMO structure of the full monomer PDVF-co-MEH-PV simulated using the B3PLY method and 6-31 G basis set.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation